Integration of short-end injection mode into electrophoretically mediated microanalysis - Nemec, Tomás; Glatz, Zdenek (Journal of chromatography. A, 2007)
The possibility of integration of the short-end injection mode in the EMMA methodology is demonstrated in this work on the kinetic studies of haloalkane dehalogenase and rhodanese enzymatic reactions. The essential validations of the EMMA methods combined with the short-end and long-end injection modes were performed first to confirm their accuracy. The qualitative and quantitative parameters of both approaches such as repeatabilities of migration times and peak areas, limits of detection and correlation coefficients were in acceptable ranges. In addition, estimated Michaelis constants for the corresponding substrate(s) were comparable being in accordance with previous literature data. Moreover, the ping-pong reaction mechanism of rhodanese reaction was confirmed by means of both injection modes. This combination thus preserves the benefits of these instrumental approaches. Whereas the short-end injection procedure brought 5-6.5 times reduction of the analysis time and 2.5-4 times increase of the sensitivity, the EMMA methodology allowed full automatization of the assays while the whole kinetic studies needed only 20 microl of corresponding enzyme preparation.
Keywords: Reproducibility of Results; Substrate Specificity; reprodukovatelnost výsledků; hydrolasy; substrátová specifita; Electrophoresis, Capillary; Thiosulfate Sulfurtransferase; Hydrolases; elektroforéza kapilární; thiosulfátsulfurtransferasa